Microscope integrated optical coherence tomography system combined with augmented reality - Tang, Ning; Fan, Jinyu; Wang, Pinghe; Shi, Guohua (Optics express, 2021)
One of the disadvantages in microscope-integrated optical coherence tomography (MI-OCT) systems is that medical images acquired via different modalities are usually displayed independently. Hence, surgeons have to match two-dimensional and three-dimensional images of the same operative region subjectively. In this paper, we propose a simple registration method to overcome this problem by using guided laser points. This method combines augmented reality with an existing MI-OCT system. The basis of our idea is to introduce a guiding laser into the system, which allows us to identify fiducials in microscopic images. At first, the applied voltages of the scanning galvanometer mirror are used to calculate the fiducials’ coordinates in an OCT model. After gathering data at the corresponding points’ coordinates, the homography matrix and camera parameters are used to superimpose a reconstructed model on microscopic images. After performing experiments with artificial and animal eyes, we successfully obtain two-dimensional microscopic images of scanning regions with depth information. Moreover, the registration error is 0.04 mm, which is within the limits of medical and surgical errors. Our proposed method could have many potential applications in ophthalmic procedures.